Power analysis of multi-legged systems - Silva, Manuel (2019)
This paper studies periodic gaits of multi-legged robot locomotion systems based on dynamic models. The purpose is to determine the system performance during walking and the best set of locomotion variables that minimizes the optimization indices. For that objective the precribed motion of the robot is completely characterized in terms of several locomotion variables such, gait, duty factor, body height, step length, stroke pitch, foot clearance, leg links length, foot-hip offset, body and legs mass and cycle time. In this perspective, we formulate four performance measures of the walking robot namely, the foot locomobility index, the mean absolute power, the mean power dispersion and the mean power lost in the joint actuators per walking distance. A set of model-based experiments reveals the influence of the locomotion variables in the proposed indices.